Association study of a functional promoter polymorphism of the X‐box binding protein 1 gene in Japanese patients with schizophrenia - WATANABE, YUICHIRO; FUKUI, NAOKI; MURATAKE, TATSUYUKI; AMAGANE, HIDEKI; KANEKO, NAOSHI; NUNOKAWA, AYAKO; SOMEYA, TOSHIYUKI (Psychiatry and clinical neurosciences, 2006)
The functional promoter polymorphism −116C/G of the X‐box binding protein 1 (XBP1) gene was found to be associated with schizophrenia in Han Chinese and Japanese subjects, although contradictive negative findings were also reported in European populations. To confirm this association in a Japanese population, the authors conducted a case‐control association study. There was no significant difference in both genotype and allele frequencies between the patients and control subjects, suggesting that the XBP1 –116C/G polymorphism might not confer increased susceptibility for schizophrenia in a Japanese population. However, further studies using a larger sample with detailed clinical data should be performed in several populations.